La evaluación de la calidad de vida del paciente oncológico. El grupo de calidad de vida de la EORTC - Arraras, Juan Ignacio; Martínez, Maite; Manterota, Ana; Laínez, Nuria (Psicooncología, 2004)
The aim of the present work is to introduce to the field of Quality of Life assessment in cancer patients. Its measurement plays a big role in the clinical trials and in the clinical practice. The European Organization of Research and Treatment of Cancer (EORTC) has a study group on Quality of Life. This group has created an assessment system composed of a core questionnaire for Quality of Life measurement and some modules for different treatments and tumours, that complete it. The Oncology Department of the Hospital of Navarre has been collaborating in this Group since 1992. Some EORTC questionnaires are presented. Also a Quality of Life study performed in a sample of breast cancer patients who were in a follow up period long after the end of their treatment.